Genetic structure of the savannah elephant population (Loxodonta africana (Blumenbach 1797)) in the Kavango-Zambezi Transfrontier Conservation Area - Van Aarde, Rudi J. (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.